2019
DOI: 10.1177/2050312119846792
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exposure in garage workers and related health risks on the biochemical levels: A comparative study in Harar town, eastern Ethiopia

Abstract: Objectives: Occupational exposure to chemicals causes a wide range of biological effects depending on the level and duration of exposure. The current study is intended to determine the differences in biochemical levels among garage workers compared with occupationally nonexposed participants in Harar town, eastern Ethiopia. Methods: A comparative cross-sectional study was conducted in Harar town, eastern Ethiopia. Thirty (30) garage workers were selected and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(44 reference statements)
0
2
1
Order By: Relevance
“…Similar findings have been documented in literature. 17 The present study revealed no significant difference in the mean total bilirubin level in cable factory workers than in control subjects (p>0.05). However, the direct bilirubin level was significantly increased in workers compared with control subjects (p<0.05).…”
Section: Discussioncontrasting
confidence: 66%
“…Similar findings have been documented in literature. 17 The present study revealed no significant difference in the mean total bilirubin level in cable factory workers than in control subjects (p>0.05). However, the direct bilirubin level was significantly increased in workers compared with control subjects (p<0.05).…”
Section: Discussioncontrasting
confidence: 66%
“…Most child labor occurs in developing countries and this problem is continuously increasing. Combination of economic and social factors was responsible for the increasing prevalence of child labor (Thévenon and Edmonds 2019).Car repair workers are exposed to different hazards, including dangerous chemicals in addition to hard work, improper work posture, long working hours and load lifting which increase the risk of occupational illnesses and injuries among them (Menicagli et al, 2018 andAtaro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanic is a professional potentially exposed to several chemical compounds (Ataro et al, 2019). Some of these chemicals or mixture of chemicals such as diesel engine exhaust, polycyclic aromatic hydrocarbons, asbestos, trichloroethylene and benzene are classified as carcinogenic to humans (Group 1) by the International et al, 2007;Khlifi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%